Testing the moderating role of environmental audits in the relationship between the carbon tax and renewable energy consumption: Evidence from Japanese manufacturing firms - Shahid Amin; Shoaib Aslam; Javed Iqbal; Muhammad Kashif Imran (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Global warming and climate change are the outcomes of excessive carbon emissions (CO2) from the consumption of fossil fuels. To reduce the volume of CO2 and to overcome this challenging environmental problem, it is imperative to encourage renewable energy consumption (REC). Furthermore, environmental regulations can also play a crucial role in promoting sustainable business practices. Thus, the primary aim of this research is to examine the impact of the carbon tax on REC. The random-effects regression model is applied through STATA 16 by using a panel of 1080 manufacturing firm-year observations from Japan for the period 2004-2019. We find a significant positive relationship between the carbon tax and REC. Due to the carbon taxation, businesses shift to renewable energy as it reduces CO2 and improves corporate environmental performance (CEP). Further, the secondary objective of this research is to examine the moderating role of environmental audits between the carbon tax and REC relationship. The empirical results confirm that environmental audits positively moderate the relationship between the carbon tax and REC. The findings of this study are in line with the stakeholder theory because mainly the environmental protection is an outcome of stakeholders' pressure. Furthermore, the results and implications of this study are helpful for regulators, environment policymakers, environment managers, investors, and environmentalists. This research study is unique because it is among the very few studies that have explored the impact of the carbon tax on REC in the corporate sector
Keywords: 330; renewable energy; carbon tax; environmental audits; environmentalmanagement systems; Tokyo Stock Exchange